Small hospitals matter: insights from the emergence and spread of vancomycin-resistant enterococci in 2 public hospitals in inner Brazil - Feltrin Correa, Adriana Aparecida [UNESP]; Campos Pignatari, Antonio Carlos; Silveira, Monica da [UNESP]; Cabral Mingone, Roberta Cristina; Sales Oliveira, Vinicius Gomes de; Castelo Branco Fortaleza, Carlos Magno [UNESP] (Elsevier B.V., 2015)
Although vancomycin-resistant enterococci (VRE) are reported in Brazil since 1996, data on their impact over settings of different complexity are scarce. We performed a study aimed at identifying determinants ofVRE emergence and spread in a public hospital consortium (comprising 2 hospitals, with 318 and 57 beds) in inner Brazil. Molecular typing and case-control studies (addressing predictors of acquisition or clonality) were performed. Among 122 authocthonous isolates, 106 were Enterococcus faecium (22 clones), and 16, Enterococcus faecalis (5 clones). Incidence was greater in the small-sized hospital, and a previous admission to this hospital was associated with greater risk of VRE colonization or infection during admission to the larger one. Overall risk factors included comorbidities, procedures, and antimicrobials (piperacillin-tazobactam, cefepime, and imipenem). Risk factors varied among different hospitals, species, and clones. Our findings demonstrate that VRE can spread within low-complexity facilities and from these to larger hospitals. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Vancomycin-resistant enterococci; Epidemiology; Case-control; Pulsed-field gel electrophoresis